Study on changes in serum irisin level in free-flap transplantation and the correlation of serum irisin level with flap blood flow - Xianyao Tao; Xiaoyun Pan; Gang Zhao; Yongjun Rui (Heliyon)
Background and aims: The beneficial effect of myokine irisin on ischemia-reperfusion of skin flaps has been rarely reported in clinical studies. This study was designed to determine whether irisin plays a protective role in flap transplantation and identify the factors affecting serum irisin levels. Materials and methods: We analyzed the changes in serum irisin levels and flap blood flow before and after surgery in 40 patients who underwent skin-flap transplantation. Factors affecting serum irisin levels were analyzed by metabolic parameter measurements. Results: Preoperative serum irisin levels were positively correlated with blood flow in the skin flap 7 days post-surgery. The increase in serum irisin levels in the first 3 days after surgery positively correlated with flap blood flow. A longer duration of high-intensity exercise, higher skeletal muscle content, lower body mass index, and waist-to-hip ratio were associated with higher irisin levels. Fasting blood glucose and glycosylated hemoglobin levels showed significant negative correlations with serum irisin levels. Several other indicators, including sex, were not associated with serum irisin levels. Conclusions: Serum irisin levels benefit blood flow recovery during flap transplantation. Better outcomes may be achieved by adjusting the timing and intensity of the exercise and controlling the patient's body size.